2022
DOI: 10.1038/s41467-022-31315-2
|View full text |Cite
|
Sign up to set email alerts
|

High stress twinning in a compositionally complex steel of very high stacking fault energy

Abstract: Deformation twinning is rarely found in bulk face-centered cubic (FCC) alloys with very high stacking fault energy (SFE) under standard loading conditions. Here, based on results from bulk quasi-static tensile experiments, we report deformation twinning in a micrometer grain-sized compositionally complex steel (CCS) with a very high SFE of ~79 mJ/m2, far above the SFE regime for twinning (<~50 mJ/m2) reported for FCC steels. The dual-nanoprecipitation, enabled by the compositional degrees of freedom, contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…These hierarchical A2 phases dramatically strengthen the friction interface through dislocation bypassing, resulting in high strain hardening, which, in turn, interrupts the local strain softening and damage initiation caused by the shearable matrix phase [ 5 , 50 ]. At higher sliding-induced deformations, high stress level, which arises from the complex interactions between dislocations and nanoprecipitates, is capable of activating DTs even in the A1 phase with high SFE [ 60 ]. The ensuing formation of nano-DTs allows for the continuous accumulation of dislocations as sustainable sources of high-density dislocation storage, further hardening and toughening the worn subsurface layer [ 10 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…These hierarchical A2 phases dramatically strengthen the friction interface through dislocation bypassing, resulting in high strain hardening, which, in turn, interrupts the local strain softening and damage initiation caused by the shearable matrix phase [ 5 , 50 ]. At higher sliding-induced deformations, high stress level, which arises from the complex interactions between dislocations and nanoprecipitates, is capable of activating DTs even in the A1 phase with high SFE [ 60 ]. The ensuing formation of nano-DTs allows for the continuous accumulation of dislocations as sustainable sources of high-density dislocation storage, further hardening and toughening the worn subsurface layer [ 10 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The spatial resolution at 200 kV was exploited (typical TEM-STEM accelerating voltages are 60-300 kV, in contrast to the few to tens of kV used in SEM-STEM) to perform a detailed study of the samples. Samples under low-angle annular dark field (LAADF) conditions were characterised, highly sensitive to lattice strain and defects [35,36], thus allowing the identification of crystal domains (i.e., grain boundaries), including nanometric crystal grains. Figure 10 shows LAADF images of 0A and 1C specimens before and after the drawing test, in an area free of residual martensite.…”
Section: Microstructure Analysis Of Bcc After Drawing Testmentioning
confidence: 99%
“…However, deformation twinning in this study was insignificantly near the middle of the crack extended within the A700 specimen at both RT and LNT (see Figure 8). Except for SFE, the twinning behavior is also strongly dependent on grain size [33,[43][44][45][46]. Rahman et al [43] indicated that twin initiation stress increased with the decrease in grain size in TWIP steel with grain size of 0.7-84 µm during cyclic tensile deformation.…”
Section: Microstructure Characterization After Impact Testsmentioning
confidence: 99%